Riflessioni sulla psichiatria di transizione alla luce della teoria della nascita - Petrucci, Manuela (Il sogno della farfalla, 2023)
During the first years of 2000, J.J. Arnett studied and empirically demonstrated a temporal prolongation of the concept of “youth”, in the familiar, cultural, and educational context, extending it from adolescence until the age of 25-30. He defined this period with the expression of “emerging adulthood”, which has then been identified as a consequence of socio-cultural changes starting from the 90s, in the population of industrialized Western countries. This finding stimulated the establishment of a new specific branch in psychiatry termed as Transition psychiatry, which has as its object of research the definition of the characteristics, requirements and potential concerns related to this phase of life. In this framework, the author discusses and explores some critical points of this approach in the light of the Human Birth Theory.